2021
DOI: 10.1186/s12886-021-02172-2
|View full text |Cite
|
Sign up to set email alerts
|

Refractive errors and risk factors for myopia in infants aged 1–18 months in Tianjin, China

Abstract: Background Infancy is the of a child’s visual development. Refractive errors, especially myopia, are a common vision disorder. Thus, the purpose of this study was to explore refractive errors and risk factors for myopia among infants aged 1–18 months in Tianjin, China. Methods A total of 583 infants aged 1–18 months participated in this cross-sectional study at Tianjin Women’s and Children’s Health Center in China from February 2019 to November 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…In this study, clients having a positive family history of refractive error increase the odds of having refractive errors by 3.94 times (p < 0.001). Studies done in India, 37 Bangladesh, 36 China 48 and Hawassa, Ethiopia 18 agree with this study finding. This could explain why, it might be, the parental history of refractive error was considered a marker for both genes and a shared family environmental exposure.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, clients having a positive family history of refractive error increase the odds of having refractive errors by 3.94 times (p < 0.001). Studies done in India, 37 Bangladesh, 36 China 48 and Hawassa, Ethiopia 18 agree with this study finding. This could explain why, it might be, the parental history of refractive error was considered a marker for both genes and a shared family environmental exposure.…”
Section: Discussionsupporting
confidence: 87%
“…Te mean SEQ was found to be 2.49 ± 1.29 D in these infants, consistent with the reported data, indicating that most infants under 3 months of age exhibited approximately 2.00-3.00 D of hyperopia. [20][21][22] Our fndings revealed that Spot photoscreener underestimated SEQ by 2.33 D compared to cycloplegic retinoscopy in these infants. With induction of cycloplegia by tropicamide 0.5% and phenylephrine 0.5% eye drops, the Spot photoscreener showed a good agreement with retinoscopy in SEQ, with the diference narrowing to −0.01 D. However, the Spot photoscreener exhibited a higher cylindrical power measurement with a diference of approximately 0.20 D, while it had a better ability to measure astigmatism in J 0 than J 45 .…”
Section: Discussionmentioning
confidence: 61%
“…The mean SEQ was 2.49 ± 1.29D in these young infants, which was consistent with the reported data, illustrating that most infants under their rst 3 months have approximately 2.0-3.0 D of hyperopia. (20)(21)(22) Our results revealed that Spot photoscreener underestimated SEQ by 2.33D compared to the cycloplegic retinoscopy in these infants. With induction of cycloplegia by compound tropicamide 0.5% and phenylephrine 0.5% eye drops, Spot photoscreener showed a good agreement with retinoscopy in SEQ and the difference discriminated to -0.01D.…”
Section: Discussionmentioning
confidence: 68%